Design of Financial Information Systems at SMK Mandiri 02 Balaraja - Fikriyah Fikriyah; Winanti Winanti; Mustar Aman; Adiyanto Adiyanto; Masduki Asbari (UJoST- Universal Journal of Science and Technology, 2022)
SMK Mandiri 02 Balaraja is a Vocational High School accredited “B”, which is located on Jl. Raya Kresek Km.0,5 Balaraja, Kota Tangerang, Banten. The payment system carried out at SMK Mandiri 02 Balaraja, currently still using the conventional system, so It takes time. The data collection method used in this activity Includes the method of observation and literature study, while the method of data analysis The data uses the waterfall model design method, the design model The ones used are UML, visual basic, and Microsoft Access as database. With this system, it is hoped that it can help schools in reducing errors that occur in payment transactions.